A framework for successful IoT adoption in agriculture sector: a total interpretive structural modelling approach. (29th October 2020) - Singh, Surabhi; Haneef, Farha; Kumar, Sumit; Ongsakul, Viput
The paper identifies the factors that build a framework of Internet of Things (IoT) adoption in agriculture by using modified TISM (total interpretive structural modelling). This study uses modified total interpretive structural modelling (m-TISM) and MICMAC methods for developing and analysing the relationship between elements that impact adoption of IoT in the agricultural sector. In this process, a framework for successful IoT adoption in this sector is devised. Through an extensive literature review, this study identifies eight factors that can influence the adoption of IoT in agriculture. The result shows that government initiative, crop management, irrigation management, and soil quality management have high driving and low dependence power. Technology is the linkage factor. The interoperability and reliability, control and automation, privacy and security, and IoT adoption have high dependence power. In this study, m-TISM is used to illustrate the relationship and describe the logic between different IoT adoption factors. The study has implications for academicians and practitioners.